Bonding of thermoplastic microfluidics by using dry adhesive tape. Issue 51 (17th August 2020) - Tsao, Chia-Wen; Syu, Wan-Ci
Abstract : We investigated dry adhesive bonding of thermoplastic microfluidics. The bonding performance is correlated to the air bubble encapsulation and Saffman–Taylor finger formation phenomena at the interface. Abstract : In this study, we investigated the effects of adhesive tape structure, adhesive tape thickness (30, 60, and 80 μm), and bonding time (5 and 15 seconds) on the bonding of inflexible and flexible substrates. We performed microchannel bonding by using a manual scraper press or a hot press machine. Rapid prototyping and mass production capabilities were achieved in the dry adhesive tape bonding of polymer microfluidic systems with both the aforementioned approaches. With process control, 95.16% and 99.53% bonding coverage could be achieved for the inflexible and flexible substrates, respectively, by using a manual scraper press. When using a press machine, the bonding coverage could be further enhanced to 99.24% for the inflexible substrates and 99.81% for the flexible substrates. Due to the viscoelastic nature of the adhesive layer in the adhesive tapes, we observed Saffman–Taylor finger and air bubble formation around the microchannel under high pumping pressure. The results indicated that the probability of Saffman–Taylor finger formation was lower and the bonding pressure was higher when using the thinner adhesive tape than when using thicker tape. Moreover, due to their rigidity, the inflexible substrates exhibited a higher bonding strength than the flexible substrates did. Bonding stability tests indicated that the bonded substrates had high bonding quality and bonding strength under long-term storage of up to 60 days.